6x-3=4(x+22)

Simple and best practice solution for 6x-3=4(x+22) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 6x-3=4(x+22) equation:


6x-3=4(x+22)

We simplify the equation to the form, which is simple to understand
6x-3=4(x+22)

Reorder the terms in parentheses
6x-3=+(+4x+88)

Remove unnecessary parentheses
+6x-3=+4x+88

We move all terms containing x to the left and all other terms to the right.
+6x-4x=+88+3

We simplify left and right side of the equation.
+2x=+91

We divide both sides of the equation by 2 to get x.
x=45.5

See similar equations:

| -11+4n=5-(11+17) | | (x^3-x^2-2)=0 | | .7(-3X-2)=3.5+1 | | -11+4n=5-(11+12) | | 6x+-10=110 | | 5x(x^3-x^2-2)=0 | | 20+2.50(19)=x | | 20+2.50(20)=x | | 20+2.50(18)=x | | 20+30+p=180 | | -9.1=k-6.3 | | 20+2.50(17)=x | | 3.2+d=5 | | 5x^2+41x-54=0 | | 20+2.50(16)=x | | 7(n-7)(8n-7)=0 | | 2x-2(x+1)=3 | | 60+19x+5.75x=159 | | -30=j-10+11j | | 3y-6=-2y-6 | | 180-(19x+4)=y | | (4x+3)(3x^2+3x+1)= | | 3m-4=6m | | 1d/2d-3/4=3d/5D | | R=s-5 | | 20+2.50(15)=x | | 10=.25(b-12) | | 12(2x+3)-3(i+7x)=0 | | -3m+5(1+m)=6+2m | | 12t^2-7t+1=0 | | 5x+7-3x=-8+3x | | 55+8x=25 |

Equations solver categories